2015
DOI: 10.1007/s10695-015-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Digestive system development and study of acid and alkaline protease digestive capacities using biochemical and molecular approaches in totoaba (Totoaba macdonaldi) larvae

Abstract: The present study aimed to describe and understand the development of the digestive system in totoaba (Totoaba macdonaldi) larvae from hatching to 40 days post-hatch (dph) from morphological and functional perspectives. At hatch, the digestive system of totoaba was undifferentiated. The anus and the mouth opened at 4 and 5 dph, respectively. During exogenous feeding, development of the esophagus, pancreas, liver and intestine was observed with a complete differentiation of all digestive organs. Expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…The data in the present study showed the presence of the transcript genes in eel larvae from hatching to P20 in accordance with other studies reporting on the European eel (Politis et al, 2018), Anguilla japonica (Kurokawa et al, 2002;Murashita et al, 2013;Pedersen, 2003) and other marine species, such as totoaba, gilthead seabream, Pacific bluefin tuna, Asian seabass, Atlantic cod, European seabass and Senegal sole (Galaviz et al, 2015;Mata-Sotres et al, 2016;Murashita et al, 2014;Srichanun et al, 2013;Zambonino-Infante et al, 2008).…”
supporting
confidence: 93%
“…The data in the present study showed the presence of the transcript genes in eel larvae from hatching to P20 in accordance with other studies reporting on the European eel (Politis et al, 2018), Anguilla japonica (Kurokawa et al, 2002;Murashita et al, 2013;Pedersen, 2003) and other marine species, such as totoaba, gilthead seabream, Pacific bluefin tuna, Asian seabass, Atlantic cod, European seabass and Senegal sole (Galaviz et al, 2015;Mata-Sotres et al, 2016;Murashita et al, 2014;Srichanun et al, 2013;Zambonino-Infante et al, 2008).…”
supporting
confidence: 93%
“…Oligonucleotides for digestive enzymes and reference genes were selected from those reported in other species. Trypsin ( tryp ) and ribosomal 18S‐rRNA ( 18S ) were reported for spotted rose snapper (Moguel‐Hernández et al, ); leucine aminopeptidase ( lap ) and alpha‐tubulin ( tub‐α ) were reported for Asian seabass (Srichanun, Tantikitti, Utarabhand, & Kortner, ); pepsin ( pep ) was reported for totoaba (Galaviz et al, ). The oligonucleotides of digestive enzymes and reference genes used for qPCR analyses are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Totoaba was placed on the endangered list of the Convention on International Trade in Endangered Species (CITES) and, in 1979, was included in the US Endangered Species list (Barrera‐Guevara, ). Protocols on reproduction, larval development and juvenile nutrition were developed as dedicated research was conducted, highlighting the high potential of commercial totoaba aquaculture (Galaviz et al., ; López, Flores‐Ibarra, Bañuelos‐Vargas, Galaviz & True, ; Trejo‐Escamilla, Galaviz, Flores‐Ibarra, Álvarez González & López, ; True, Loera & Castro, ). In a previous study of totoaba, green liver was detected when fish were fed a commercial diet with soybean meal (SBM) and soy protein concentrate (SPC) without taurine supplementation (López et al., ).…”
Section: Introductionmentioning
confidence: 99%